The Strategy Of Bank Negara Indonesia (BNI) In Food Estate Development As National Resilience In The Era Of The Covid-19 Pandemic From A Geopolitical And Geostrategic Perspective - Henny Saptatia Drajati Nugrahani; Audrey G. Tangkudung; Abiwodo Abiwodo (CV. Syntax Corporation Indonesia, 2020)
Food estate is a strategy that is compatible to be applied in a pandemic situation, where disease outbreaks are a form of non-conventional threat to national security. Indonesia's food security is an issue domestic especially in facing the Covid-19 Pandemic. The purpose of this study is to determine the Implementation Strategy of Bank Negara Indonesia (BNI) in Food Estate Development as National Defense in the Era ofthe Covid-19 Pandemic. The method used in this research is qualitative research with literature study method. The results of this study are the implementation of the Food estate program, the government of the Republic of Indonesia collaborates with BNI Bank to provide distribution of funds to farmers through the People's Business Credit (KUR). With low interest rates, easy terms, and payment methods through a simple scheme, KUR can provide benefits for farmers, especially to increase agricultural productivity.